Simulation of droplet coalesce using lattice Boltzmann method - Mohamad Rizam, Zenudin (2009)
In this project, a single component multiphase (SCMP) LBM is proposed to simulate the phenomenon of droplet coalesce using Lattice Boltzmann method. The basic idea is to see on how two stationary droplet without collision will merge together. Besides, effect of the height on droplet’s neck or interface is studied in this thesis. A development on Lattice Boltzmann method is storied from early where it is evolved by Lattice Gas approach and it is continue with the Navier-Stokes equation and collision theory. A derivation of the Lattice Boltzmann scheme from the classical Boltzmann equation is dicussed in detail. According to the problems, a single component multiphase (SCMP) LBM is used or involved in the equation in order to solve more phase of fluids. Before that, investigation on non ideal fluid is discussed using van der Waals fluids where the critical constant of pressure, volume and temperature is solved. By doing this, it will tell the characteristic of the liquid and gas phase. From the Maxwell equal area construction, the value of macroscopic variables, density of fluids is determined which will be code in the algorithm. Algorithm of multiphase LBM involving the initial condition, streaming step, collision step and boundary condition is coded to done the simulation. The progress of droplet coalesce will occur from initial until steady state. The study on droplet coalesce proven where the neck height of droplets will increase as the time step increased. The two droplets will merge together until steady state and become one big droplet.